Um grito na terra: a emergência de um movimento para a transição na Associação das Entidades de Feira de Santana – ADEFS (1980-1985) - Araujo, Hugo Damasceno de (2018)
The object of investigation this research is the trajectory of the Association of Entities of Feira de Santana (ADEFS), entity that gathered in the decade of 1980 several organizations of workers and other groups that made up the society of Feirense, such as association of residents and student associations. Some editions of the newspaper O Grito da Terra and the internal documents of ADEFS were analyzed, which allowed to identify the project that the organization defended for the country; besides identifying the contribution of the association for the social struggles in Feira de Santana and region. The methodological reference was the attempt to analyze the object dialectically. Interviews were conducted with Professor José Carlos Barreto de Santana and with Mr. Edvaldo Rios, president of the Association of New Street Residents (AMORUN) and members of ADEFS during the temporal cut of this research. The bibliographic survey helped to situate ADEFS in the process of intensifying social struggles in the Brazilian historical context. The confrontation of these sources with the theses on the political ascent of the working class allowed to verify to what extent they apply to the case of ADEFS and the working class of Feirense. This synthesis effort presents the results of a research on the social movement that organized the newspaper O Grito da Terra and ADEFS in the early 1980s to manage the newspaper. The historical terrain on which the movement was organized was marked by intense social struggles at national and international level, which provided the conditions for its organization and demarcated the senses. Subsequently, questions about unity and diversity within the movement, considering its project, its internal contradictions and the struggles to which it gave visibility and caught. The first chapter is an attempt to situate the historical ground on which the newspaper O Grito da Terra and ADEFS were organized. The second chapter is an attempt to capture the sense of the diagnosis of Brazilian society, of the project, of the internal conflicts and of the struggles of the movement.